Pentingnya Wawasan Perspektif Global dalam Menghadapi Tantangan di Era Society 5.0 Bagi Calon Pendidik Maupun Pendidik. - Sabrina Anggun Kusuma; Taqiyyah Karimah (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this researcher is to find out the extent of the influence related to the importance of a global perspective is very important, because in essence we as citizens of the world cannot escape from social life in which there is a lot of diversity such as views, languages, religions, customs, cultures and so on. A global perspective teaches prospective educators and educators to understand how to deal with global problems, one of which is facing challenges in the Era of Society 5.0. The results of this study indicate that the insight of a global perspective is very important for prospective educators and educators to face various challenges in the Era of Society 5.0 and provide experience to prospective educators and educators regarding their views on the Era of Society 5.0.